Non-coding RNAs Function as Immune Regulators in Teleost Fish - Wang, Man; Jiang, Shuai; Wu, Wei; Yu, Fei; Chang, Wenguang; Li, Peifeng; Wang, Kun (Frontiers in Immunology, 2018)
Non-coding RNAs (ncRNAs) are functional RNA molecules that are transcribed from DNA but not translated into proteins. ncRNAs function as key regulators of gene expression and chromatin modification. Recently, the functional role of ncRNAs in teleost fish has been extensively studied. Teleost fish are a highly diverse group among the vertebrate lineage. Fish are also important in terms of aquatic ecosystem, food production and human life, being the source of animal proteins worldwide and models of biomedical research. However, teleost fish always suffer from the invasion of infectious pathogens including viruses and bacteria, which has resulted in a tremendous economic loss to the fishing industry worldwide. Emerging evidence suggests that ncRNAs, especially miRNAs and lncRNAs, may serve as important regulators in cytokine and chemokine signaling, antigen presentation, complement and coagulation cascades, and T cell response in teleost fish. In this review, we summarize current knowledge and understanding of the roles of both miRNAs and lncRNAs in immune regulation in teleost fish. Molecular mechanism insights into the function of ncRNAs in fish immune response may contribute to the development of potential biomarkers and therapeutic targets for the prevention and treatment of fish diseases.